Sound Calculation Simulation System for Distribution of Chair Parliament Using Hare Quota and Sainte Lague Methods - Arif Pratama; Arif Arizal; Syariful Alim (Fakultas Teknik Universitas Bhayangkara, 2019)
The conversion of the ballot for the division of parliamentary seats has become one of the historical points inthe development of the democratic order in Indonesia. How not, through a plenary session, the DPR RI finally finalizesthe discussion and decision making on the Election Bill proposed by the government. Conversion of votes is one of thecrucial issues to get the word consensus in the House of Representatives, because the method of voting conversionused will greatly determine the acquisition of seats for a political party. For example, if using the quota method, aparty can get 5 seats, but it is not certain if the calculation method uses the Sainte Lague method, it could be that oneparty will get 4 to 6 seats. That is why the voting conversion method is one of the main variables of an electoral system.The method of converting votes is the procedure for calculating the results of elections to determine theacquisition of seats for political parties in representative institutions based on the results of the acquisition of validvotes of each political party participating in the election. The Hare Quota method is characterized by a calculationmethod using the Number of Voters Dividers (BPP) which divides the total number of valid voting votes by the numberof seats allocated to one particular constituency, and always has the remaining choice of votes that requirescalculation at the next stage for the remaining votes of choice / residual the chair is the Sainte Lague method (theremaining votes are voted on).